The Effect of a Training Program Using High-Intensity Interval Training on Several Physiological Variables Among Young Wrestlers - Ramadhan Taha, Taha (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2024)
This study aimed to examine the effects of a high-intensity interval training (HIIT) program on the physiological variables of young wrestlers. The significance of this study lies in its potential to identify effective training strategies to enhance the physiological capabilities of wrestlers, which are crucial for optimal performance. Despite the potential benefits of HIIT, research on its effects on young wrestlers is limited. The study utilized a pre- and post-test experimental design involving 14 young wrestlers from the Zakho Sports Club who were divided into control and experimental groups, each comprising seven wrestlers. The experimental group underwent a 9-week HIIT program, whereas the control group underwent a traditional training program. The physiological variables assessed included blood pressure, heart rate, lactic acid concentration, and anaerobic and aerobic powers. The results indicated significant improvements in the experimental group in terms of resting heart rate, heart rate after effort, lactic acid concentration, and aerobic power but not in blood pressure or anaerobic power. These findings confirm that HIIT can effectively enhance the physiological efficiency of young athletes and provide valuable methodological contributions to training programs for young wrestlers. This research demonstrates that HIIT effectively enhances athletes' physiological capacity and technical performance. This conclusion validates the idea that customized high-intensity and interval-based training can lead to substantial and advantageous physiological improvements in young wrestlers.